The establishment of an ISO compliant cancer biobank for Jordan and its neighboring countries through knowledge transfer and training. - BARR, MARTIN; GATELY, KATHY; O'BYRNE, KEN (My University, 2014)
Research studies aimed at advancing cancer prevention, diagnosis, and treatment depend on a number of key resources, including a ready supply of high-quality annotated biospecimens from diverse ethnic populations that can be used to test new drugs, assess the validity of prognostic biomarkers, and develop tailor-made therapies. In November 2011, KHCCBIO was established at the King Hussein Cancer Center (KHCC) with the support of Seventh Framework Programme (FP7) funding from the European Union (khccbio.khcc.jo). KHCCBIO was developed for the purpose of achieving an ISO accredited cancer biobank through the collection, processing, and preservation of high-quality, clinically annotated biospecimens from consenting cancer patients, making it the first cancer biobank of its kind in Jordan. The establishment of a state-of-the-art, standardized biospecimen repository of matched normal and lung tumor tissue, in addition to blood components such as serum, plasma, and white blood cells, was achieved through the support and experience of its European partners, Trinity College Dublin, Biostór Ireland, and accelopment AG. To date, KHCCBIO along with its partners, have worked closely in establishing an ISO Quality Management System (QMS) under which the biobank will operate. A Quality Policy Manual, Validation, and Training plan have been developed in addition to the development of standard operating procedures (SOPs) for consenting policies on ethical issues, data privacy, confidentiality, and biobanking bylaws. SOPs have also been drafted according to best international practices and implemented for the donation, procurement, processing, testing, preservation, storage, and distribution of tissues and blood samples from lung cancer patients, which will form the basis for the procurement of other cancer types. KHCCBIO will be the first ISO accredited cancer biobank from a diverse ethnic Middle Eastern and North African population. It will provide a unique and valuable resource of high-quality human biospecimens and anonymized clinicopathological data to the cancer research communities world-wide.
PUBLISHED
Keywords: ISO compliant Biobank; Cancer; Biomedical sciences